Judas Iscariot: The Archetypal Betrayer and DeMille’s Cine-Biblical Salvation within The King of Kings (1927) - Anton Karl Kozlovic (European Journal of American Studies)
Cecil B. DeMille, the legendary cofounder of Hollywood, progenitor of Paramount studio, and unsung Christian auteur was a master of the American biblical epic whose indelible classics became the template for numerous ancient epics thereafter. Utilising humanist film criticism as the guiding analytical lens, the critical DeMille, film and religion literature was selectively reviewed and his silent Jesus film, The King of Kings (1927) was closely examined to reveal his dramatic construction of Judas Iscariot, which was briefly compared to some cinematic rivals to highlight its frequent superiority. Often unappreciated was DeMille’s harmonisation of the conflicting hanging versus disembowelment accounts of Judas’ demise. It was concluded that DeMille was a defter biblical filmmaker than has been hitherto appreciated. Further research into DeMille studies, Hollywood epics, and the emerging interdisciplinary field of religion-and-film is recommended, warranted, and already long overdue.